INFLUENCE OF PRODUCT QUALITY,PRICE AND BRAND IMAGE ON PURCHASING DECISIONS FOR MS GLOW COSMETICS IN TEBING TINGGI CITY WITH LABELSHALAL AS A MODERATING VARIABLE - Sarwoto; Ferdinand Simanjuntak; Rani Puspita Sari (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
This research seeks to examine the impact of product quality, pricing, and brand image on consumers' decisions to purchase Ms. Glow products in Tebing Tinggi, taking into account the moderating variable of a halal label. The study aims to ascertain whether these effects are direct or indirect in nature. It falls under the category of explanatory research, which elucidates the causal relationships among variables through hypothesis testing. The study involved a sample of 96 respondents, selected through accidental sampling, consisting of individuals who had previously purchased MS Glow products. Data analysis encompassed a Validity Test, Reliability Test, and Hypothesis Testing (t Test), and the data processing was carried out using SmartPLS version 3.0 software. The findings indicate that product quality does not exert a significant influence on purchasing decisions for Ms. Glow products in Tebing Tinggi. In contrast, pricing has a discernible impact on purchasing decisions for Ms. Glow products in the city. Furthermore, brand image plays a significant role in influencing consumers' decisions to purchase Ms. Glow products in Tebing Tinggi. However, it was observed that the presence of a halal label did not significantly affect purchasing decisions for Ms. Glow products in the city. Additionally, the halal label does not act as a moderator in influencing the relationship between product quality, pricing, and brand image on consumers' purchasing decisions for Ms. Glow products in Tebing Tinggi.